2006
DOI: 10.3138/jcfs.37.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Mothering among Korean Immigrant Working Class Women in the United States

Abstract: Based upon in-depth interviews with 22 working Korean immigrant mothers of adolescent children in Philadelphia, we examined their mothering practices in the contexts of working outside of the home to meet the economic demands of their families. We used Strauss and Corbin’s grounded theory approach in order to guide our data collection and analysis. We found that mothering practices are negotiated and reconstructed in the process of their acculturation, and further are modified depending upon the length of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…For example, recently immigrated Korean women demonstrate the flexibility of the construction of mothering in their lives as they transition from stay‐at‐home mothers in Korea to working mothers in the United States (Kim et al ). Further demonstrating the fluidity of this construct, Kim et al () found that the work that Korean women consider “mothering work” has changed within the context of resettlement, with children taking on more responsibility for tasks that were previously considered “mothering work.” Segura () offers us another example of a different formulation of motherhood and work in her research on Chicana and Mexicana mothers in the United States who view motherhood differently from one another. Chicanas viewed motherhood as something distinct from employment, working only if necessary, whereas Mexicanas viewed motherhood as including employment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recently immigrated Korean women demonstrate the flexibility of the construction of mothering in their lives as they transition from stay‐at‐home mothers in Korea to working mothers in the United States (Kim et al ). Further demonstrating the fluidity of this construct, Kim et al () found that the work that Korean women consider “mothering work” has changed within the context of resettlement, with children taking on more responsibility for tasks that were previously considered “mothering work.” Segura () offers us another example of a different formulation of motherhood and work in her research on Chicana and Mexicana mothers in the United States who view motherhood differently from one another. Chicanas viewed motherhood as something distinct from employment, working only if necessary, whereas Mexicanas viewed motherhood as including employment.…”
Section: Resultsmentioning
confidence: 99%
“…This shift in perspective highlights patterns of inequality and stratification that are central to a sociological lens. Thus, sociologists who have focused on immigrant families have noted the effects of structural constraints, such as high levels of poverty (Crosnoe 2007; Hernandez, Denton, and Macartney 2007) on parenting, on mothering practices (Kim et al. 2006), and on broader patterns of demographic change (Hernandez 2005).…”
Section: Familymentioning
confidence: 99%
“…When immigrating to the United States, Korean immigrants often experience a downward economic slide. Their professional experiences and educational backgrounds attained in Korea are not often recognized (Kim, Conway-Turner, Sherif-Trask, & Woolfolk, 2006). More often than not, Korean immigrants have to restart their careers while struggling with language barriers and limited financial means.…”
Section: The Role Of Coping Resources In Lessening Hwabyung and Deprementioning
confidence: 97%